2019
DOI: 10.1016/j.jtcvs.2018.10.137
|View full text |Cite
|
Sign up to set email alerts
|

The cost burden of clinically significant esophageal anastomotic leaks—a steep price to pay

Abstract: Objective: The purpose of this retrospective cohort study was to evaluate resource consumption of clinically significant esophageal anastomotic leaks.Methods: Between September 1, 2008, to December 31, 2014, a prospectively maintained database was queried to identify patients with grade III to IV anastomotic leaks after esophagectomy for esophageal cancer. Inflation-adjusted standardized costs were applied to billed services related to leak diagnosis and treatment, from time of leak detection to resumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Here, we arrive A few studies have addressed the economic burden arising from complications after esophagectomy. 12,13,19,20 All of these only recently published studies conclude that complications are associated with a substantial increase in costs. While Goense et al observed a per case cost increase of €4.123 for AL, 12 the median standardized costs per leak described by Agzarian et al were significantly higher with $68.296.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we arrive A few studies have addressed the economic burden arising from complications after esophagectomy. 12,13,19,20 All of these only recently published studies conclude that complications are associated with a substantial increase in costs. While Goense et al observed a per case cost increase of €4.123 for AL, 12 the median standardized costs per leak described by Agzarian et al were significantly higher with $68.296.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AL is approximately 6-24% in patients undergoing oesophagogastrostomy [2,6], with an increased postoperative mortality rate of 7.2-18.2% compared with that of 3.1-6.2% in patients without leakage. The cost burden was two-times higher for high-grade leakages in an analysis of cervical oesophagogastric anastomotic leaks after transhiatal oesophagectomy [7]. The early detection of AL is crucial since delayed treatment is associated with significant morbidity, a prolonged hospital stay, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical reoperation for anastomotic leak prolongs hospitalization, significantly delays oral nutrition, and contributes to a greater cost of care. 7 Efforts to use endoscopic stenting to reduce morbidity associated with anastomotic leak have been reported. We previously reported favorable results on 9 patients who developed postoperative esophageal anastomotic leak and underwent endoscopic stenting.…”
Section: Introductionmentioning
confidence: 99%